E-Cigarette Use and Use of Evidence-Based Smoking Cessation Methods Among American Indian Cigarette Smokers: A Cross-Sectional Analysis - Ashley L. Comiford, DrPH; Dorothy A. Rhoades, MD, MPH; Justin D. Dvorak, PhD; Kai Ding, PhD; Noah Collins; Alexandra L. Blair; Mark P. Doescher, MD, MSPH (AJPM Focus)
Introduction: Tobacco use is the leading cause of death in the U.S., and American Indian/Alaska Native people have high rates of tobacco-related diseases. Although the U.S. Food and Drug Administration–approved products and evidence-based methods exist for smoking cessation, people who smoke might use E-cigarettes as cessation aids. Whether E-cigarette use is associated with the use of evidence-based methods is unknown, particularly among American Indian/Alaska Native individuals. Methods: Using survey data collected in 2016 from 289 adult American Indian people who smoke and who reported a previous cessation attempt, the authors conducted multivariate logistic regression analyses to assess the associations between E-cigarette use and evidence-based cessation methods. Analyses were performed in 2023. Results: Individuals who currently or formerly used E-cigarettes were significantly more likely to report using nicotine replacement therapy during their last quit attempt than those who did not use E-cigarettes (current versus never AOR=4.6, 95% CI=1.9, 11.9; past versus never AOR=4.6, 95% CI=2.2, 9.8; p<0.001). Current and former E-cigarette use was significantly associated with prescription use in the unadjusted analysis but lost significance in the adjusted analysis (current versus never AOR=3.1, 95% CI=1.0, 10.5; past versus never AOR=2.7, 95% CI=1.1, 7.9; p>0.05). Individuals with current or former use of E-cigarettes were significantly less likely than individuals who never used E-cigarettes to use the cold turkey method (unassisted cessation) (current versus never AOR=0.3, 95% CI=0.2, 0.6; past versus never AOR=0.3, 95% CI=0.1, 0.7; p<0.01). Conclusions: These results suggest that persons who use E-cigarettes are more likely than individuals who do not use E-cigarettes to previously have tried nicotine replacement therapy but less likely to use the cold turkey method. A larger study is needed to determine whether individuals who use E-cigarettes are also more likely to have tried prescription medication for smoking cessation. Whether E-cigarette use impedes or encourages the use of evidence-based cessation methods is unknown.